P2_04 Making a Day Longer - Sinclair, James; Stock, Jon; Attree, Nick; Rivers, Chris (Physics Special Topics, 2011)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The rotational speed of the Earth is very gradually slowing. This paper aims to investigate the possibility of artificially increasing the length of a day by accelerating the rate at which the Earth’s spin is slowing down.